Variability of Human rDNA and Transcription Activity of the Ribosomal Genes - Chmúrčiaková, Nikola; Smirnov, Evgeny; Kurfürst, Jaroslav; Liška, František; Cmarko, Dušan (International journal of molecular sciences, 2022)
Human ribosomal DNA is represented by hundreds of repeats in each cell. Every repeat consists of two parts: a 13 kb long 47S DNA with genes encoding 18S, 5.8S, and 28S RNAs of ribosomal particles, and a 30 kb long intergenic spacer (IGS). Remarkably, transcription does not take place in all the repeats. The transcriptionally silent genes are characterized by the epigenetic marks of the inactive chromatin, including DNA hypermethylation of the promoter and adjacent areas. However, it is still unknown what causes the differentiation of the genes into active and silent. In this study, we examine whether this differentiation is related to the nucleotide sequence of IGS. We isolated ribosomal DNA from the nucleoli of human-derived HT1080 cells, and separated methylated and non-methylated DNA by chromatin immunoprecipitation. Then, we used PCR to amplify a 2 kb long region upstream of the transcription start and sequenced the product. We found that six SNVs and a series of short deletions in a region of simple repeats correlated with the DNA methylation status. These data indicate that variability of IGS sequence may initiate silencing of the ribosomal genes. Our study also suggests a number of pathways to this silencing that involve micro-RNAs and/or non-canonical DNA structures.
Keywords: RNA ribozomální 28S; DNA, Ribosomal; DNA, Ribosomal Spacer; ribozomy; DNA, Intergenic; lidé; intergenová DNA; RNA, Ribosomal, 28S; mezerníky ribozomální DNA; Humans; ribozomální DNA; Ribosomes; Base Sequence; sekvence nukleotidů